Synthesis and characterization of thermally treated Co1-xFe2+xO4 (x = 0.0 –0.8) spinel nano ferrite. Issue 1 (1st October 2022) - Parmar, C; Verma, R; Modak, S S; Mazaleyrat, F; Kane, S N
Abstract : We report the effect of surplus-Fe-content, and thermal annealing on the properties of sol gel auto-combustion synthesized Co1–x Fe2+x O4 (x = 0.0–0.8) spinel ferrites. X-ray diffraction (XRD), magnetic measurements, Fourier transform infrared (FTIR) spectroscopy, Ultraviolet–visible (UV–Vis) are used to monitor the effect of excess Fe-content, and thermal annealing dependence of properties, and correlation among them. XRD validates presence of spinel nanoferrite (31.54 – 44.89 nm) phase, minor presence of α-Fe2 O3 phase was also detected. Results reveal that variation of Fe-content leads to: i) variation of lattice-parameter, re-distribution of Fe 3+ . Co 2+ ions on A, B-site, ii) alteration of inversion degree, disorder, iii) modification of saturation magnetization due to spin disorder at surface, iv) variation of coercivity, and related grain size imply that studied ferrites are in single-multi domain overlap regions, while squareness-ratio indicates variation of inter-grain interaction, isotropic behaviour of multi-domain particles; iv) fine-tuning of bandgap (1.35 – 1.5 eV) via changes in cationic-distribution and lattice-parameter, v) variation of Debye temperature, suggests modification of lattice vibrations. Current work implies strong correlation between bandgap magnetic, structural properties.